Effect of density on Mediterranean pine seedlings using the Nelder wheel design: analysis of biomass production. (25th July 2022) - Ruano, Irene; Herrero de Aza, Celia; Bravo, Felipe
Abstract: The main objective of this study was to analyse biomass production and distribution among the constituent parts of 4-year-old Pinus pinaster and Pinus halepensis trees. Young trees were harvested from a Nelder wheel experimental site and their biomass weight was determined. With the Nelder design, the effect of stand density can be included in the biomass analysis. We analysed biomass production at test densities ranging from 1000 to 80 000 seedlings/ha by fitting two types of equations: (1) Dirichlet regressions to estimate the biomass proportions of constituent tree parts and (2) allometric equations to simultaneously predict the biomass content of constituent tree parts. Results from this innovative approach showed that the effect of stand density in tree-level biomass was significant for P. halepensis but not for P. pinaster . We observed a general increase of total biomass from P. halepensis at lower densities. More precisely, the proportion of root biomass increased at the expense of aboveground biomass, which is considered a positive effect in terms of resilience and adaptation. This new set of equations fills a fundamental knowledge gap for these species in central Spain and can readily be used by silviculturists and scientists to quantify carbon stocks for young planted forests.